2014
DOI: 10.1007/s11745-014-3981-9
|View full text |Cite
|
Sign up to set email alerts
|

BMP7 Drives Human Adipogenic Stem Cells into Metabolically Active Beige Adipocytes

Abstract: Adult humans have a substantial amount of inducible-brown (or beige) fat, which is associated with increased energy expenditure and reduced weight gain via thermogenesis. Despite the identification of key regulators of beige adipogenesis, impacts of dietary factors on adaptive thermogenesis are largely unknown, partly due to a lack of validated human cell models. Bone morphogenetic protein 7 (BMP7) is known to promote brown adipogenesis in rodent and human progenitor cells. However, controversy still surrounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 48 publications
1
46
0
Order By: Relevance
“…All protocols and procedures were approved by the Institutional Review Board at the University of Nebraska-Lincoln and King Saud University. Isolation of human adipose-derived stem cells ( h ASC) and differentiation of adipocytes were conducted as we described previously [18]. For cultures of primary mouse adipocytes, subcutaneous fat-derived stem cells were used and differentiated as we described previously [13].…”
Section: Methodsmentioning
confidence: 99%
“…All protocols and procedures were approved by the Institutional Review Board at the University of Nebraska-Lincoln and King Saud University. Isolation of human adipose-derived stem cells ( h ASC) and differentiation of adipocytes were conducted as we described previously [18]. For cultures of primary mouse adipocytes, subcutaneous fat-derived stem cells were used and differentiated as we described previously [13].…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies reported that stem cells from human WAT treated with the peroxisome proliferator-activated receptor-γ agonist rosiglitazone 79 or bone morphogenetic protein 7 80 easily differentiate toward beige adipocytes and markedly enhance oxygen consumption. In addition, bone morphogenetic protein 7-driven browning of adipocytes results in higher glucose and FA uptake than white adipocytes.…”
Section: Because [mentioning
confidence: 99%
“…In addition, bone morphogenetic protein 7-driven browning of adipocytes results in higher glucose and FA uptake than white adipocytes. 80 Browning of WAT has therapeutic potential, as humans have large amounts of WAT that may be susceptible to browning. This is nicely illustrated by a markedly increased brown fat mass and energy expenditure in patients who have a pheochromocytoma, a catecholamine-producing neuroendocrine tumor.…”
Section: Because [mentioning
confidence: 99%
“…Furthermore, lipoprotein lipase (LPL) expression in perivascular BAT depots surrounding the aorta is negatively correlated with plasma TG levels [57]. Stem cells derived from human WAT treated with with peroxisome proliferator-activated receptor γ (PPARγ) agonist rosiglitazone or bone morphogenic protein 7 (BMP7) easily differentiate into beige adipocytes and have markedly enhanced oxygen consumption [58], [59]. In a recent report, thermogenic adipocytes were reported to promote HDL lipidome remodeling in humans after cold exposure irrespective of total plasma HDL-C concentrations [60].…”
Section: Adipose Browning In Humansmentioning
confidence: 99%